1996
DOI: 10.1016/0022-328x(95)06073-6
|View full text |Cite
|
Sign up to set email alerts
|

ansa-Metallocene derivatives XXXII. Zirconocene complexes with a spirosilane bridge: syntheses, crystal structures and properties as olefin polymerization catalysts

Abstract: Chiral ansa-zirconocene complexes with a trimethylene link between the Si bridge atom and an a-position of each C s ring ligand were prepared; two representatives, with i-propyl and t-butyl groups as f3-substituents, were structurally characterized. The properties of these complexes with respect to MAO-activated propene polymerization were studied in comparison with those of their Me 2 Si-bridged analogs. The t-butyl-substituted spirosilane complex gives a polymer with relatively high content of 3, I-insertion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…Indeed, it is known that a 2,1-insertion of propylene places the methyl in a peripheral position (rather than in the direction or plane of the metal), and the resultant intermediate transition state requires less space along the direction of metal aperture to undergo a 2,1insertion. 10,71 It is worth noting that Ʃx n,2i only indicates the minimum fraction of inverted propylene units since the calculated data neglects all the inverted units contained in the methylene sequences longer than six methylene units (n 6+ ), and 1,3-enchained propylene units arising from a 2,1→1,3…”
Section: Copolymers Compositionmentioning
confidence: 99%
“…Indeed, it is known that a 2,1-insertion of propylene places the methyl in a peripheral position (rather than in the direction or plane of the metal), and the resultant intermediate transition state requires less space along the direction of metal aperture to undergo a 2,1insertion. 10,71 It is worth noting that Ʃx n,2i only indicates the minimum fraction of inverted propylene units since the calculated data neglects all the inverted units contained in the methylene sequences longer than six methylene units (n 6+ ), and 1,3-enchained propylene units arising from a 2,1→1,3…”
Section: Copolymers Compositionmentioning
confidence: 99%
“…In regard to the achievements of the use of well‐defined cationic group 4 metal complexes and their role as important olefin polymerization catalysts, numerous substitution patterns for the ancillary ligand systems have been developed do direct their catalytic activity . For example, Brintzinger et al synthesized a silaspiro zirconocene complex, which posseses C 2 ‐symmetry, and showed that this complex is able to polymerize propylene to isotactic polypropylene after activation with methylaluminoxan (MAO) to the corresponding cationic complex . In contrast a quite similar C s ‐symmetric complex affords almost only atactic polypropylene …”
Section: Introductionmentioning
confidence: 99%
“…[3]). Increasing interest in chiral ansa-metallocenes, especially of Group 4 metals, as catalysts for stereoselective reactions [3,4] has been associated with substantial efforts to develop strategies which yield the pure racemic diastereomer [5][6][7][8][9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…A different approach is the incorporation of a second linker to prevent the bis(cyclopentadienyI) ligands from isomerization [12]. Chiral, doubly bridged [13] or spirobridged [14] substituted ligand systems have recently been designed which give solely the racemic metallocenes.…”
Section: Introductionmentioning
confidence: 99%